Arabian and Saharan Dust Optical and Microphysical Properties: Synergy of CARO Limassol PollyXT Lidar, and Sun Photometer observations using GRASP algorithm - Savva, Athina; Nisantzi, Argyro; Scarlatti, Francesco; Lopatin, Anton; Hadjimitsis, Diofantos G.; Mamouri, Rodanthi-Elisavet (My University, 2025)
Earth’s atmospheric radiative energy budget is strongly influenced by aerosols in the atmosphere [1]. Desert dust from the Middle East and the Sahara/North Africa regions is considered one of the major types of atmospheric aerosols globally. The Eastern Mediterranean, particularly Cyprus, is influenced by the transport of air masses from the Sahara Desert and the Arabian Peninsula. Many studies have shown that some optical and microphysical characteristics of these two aerosol types differ [2]. A study by Nisantzi et al. (2015) [2] conducted in Cyprus, found that the Lidar ratio of Saharan dust is 53 ± 6 sr, while that of Middle Eastern dust was significantly lower, at 41 ± 4 sr at 532 nm. Additionally, the real part of the refractive index for Middle Eastern dust was higher, measured at 1.55, compared to 1.45 for Saharan dust in the 500–550 nm wavelengths [2]. The main objective of the present study is to investigate the optical and the microphysical characteristics of desert dust from both regions by utilizing the synergy between the Polarization PollyXT Raman Lidar and the Cimel sun/sky photometer, in Limassol city of Cyprus. The analysis is performed using the Generalized Retrieval of Atmosphere and Surface Properties (GRASP) algorithm.